(untitled) (Advances in Applied Mathematics and Mechanics, 2022)
The Peng-Robinson equation of state, one of the most extensively applied equations of state in the petroleum industry and chemical engineering, has an excellent appearance in predicting the thermodynamic properties of a wide variety of materials. It has been a great challenge on how to design numerical schemes with preservation of mass conservation and energy dissipation law. Based on the exponential time difference combined with the stabilizing technique and added Lagrange multiplier enforcing the mass conservation, we develop the efficient first- and second-order numerical schemes with preservation of maximum bound principle (MBP) to solve the single-component two-phase diffuse interface model with Peng-Robinson equation of state. Convergence analyses as well as energy stability are also proven. Several two-dimensional and three-dimensional experiments are performed to verify these theoretical results.